EVOLUTION OF THE PRINCIPLE OF FREEDOM OF CONTRACT AS A FUNDAMENTAL PRINCIPLE OF CIVIL LAW - Daniil A. Polynkov (Russian Studies in Law and Politics)
The article is devoted to a comprehensive study of the evolution of the principle of freedom of contract as a fundamental element of civil law. The scientific novelty of the work consists in a holistic historical and legal analysis of the formation of this principle in various legal systems, including Romano-Germanic and Anglo-Saxon. Modern challenges to the principle of freedom of contract associated with the digitalization of the economy and the emergence of new forms of contractual relations, such as smart contracts, are considered.